Chromosome 13q deletion with Waardenburg syndrome: further evidence for a gene involved in neural crest function on 13q. Issue 7 (July 1995) - Van Camp, G; Van Thienen, M N; Handig, I; Van Roy, B; Rao, V S; Milunsky, A; Read, A P; Baldwin, C T; Farrer, L A; Bonduelle, M
Abstract : Waardenburg syndrome (WS) is an autosomal dominant disorder characterised by pigmentary abnormalities and sensorineural deafness. It is subcategorised into type 1 (WS1) and type 2 (WS2) on the basis of the presence (WS1) or absence (WS2) of dystopia canthorum. WS1 is always caused by mutations in the PAX3 gene, whereas WS2 is caused by mutations in the microphthalmia (MITF) gene in some but not all families. An association of WS symptoms with Hirschsprung disease (HSCR) has been reported in many families. We report here a patient with characteristics of WS2 and a de novo interstitial deletion of chromosome 13q. We also describe a family with two sibs who have both WS2 and HSCR. In this family, all possible genes for WS and HSCR, but not chromosome 13q, could be excluded. As an association between chromosome 13q and HSCR/WS has been reported previously, these data suggest that there is a gene on chromosome 13q that is responsible for WS or HSCR or both.